Effectiveness of E-SWS Sound Waves using the Discovery Learning Model on Student Learning Outcomes - Az Zahra Murmiftah; Hidayati Hidayati; Asrizal Asrizal; Fuja Novitra (Universitas Negeri Padang in collaboration with Association of Mathematics and Natural Sciences Institution for Education of Teaching Staff Indonesia (AMLI), 2025)
Learning physics on the subject of sound waves remains a challenge because abstract concepts are often difficult for students to understand. This study aims to test the effectiveness of using E-SWS sound waves using a Discovery Learning model that has been revised in accordance with the Independent Curriculum on student learning outcomes in cognitive and psychomotor aspects. The research method used is quasi-experimental with a posttest only control group design. The research sample consisted of two classes, Phase F5 and F6, at SMA Negeri 3 Payakumbuh, with F5 as the experimental class using Discovery Learning-based E-SWS and F6 as the control class using the Discovery Learning model without E-SWS. The research instruments were multiple-choice tests to measure cognitive aspects and science process skill observation sheets for psychomotor aspects. Data analysis was conducted through a two-sample t-test. The results showed that the average posttest score for the experimental class was 89.2, which was higher than that of the control class, which was 73.7. In terms of psychomotor skills, the average score for the experimental class was 78, which was also higher than that of the control class, which was 67.5. The t-test showed that the t-count was greater than the t-table, indicating a significant difference in both aspects. It was concluded that E-SWS using the Discovery Learning model was effective in improving students' cognitive learning outcomes and science process skills.